Managing Heterogeneous Database Replication Using Persistence Layer Synchronous Replication (PLSR) - Noraziah, Ahmad; Abdalla, Ahmed N.; Beg, Abul Hashem (WULFENIA, 2013)
Distributed database replication in the heterogeneous system is a very promising and challenging platform which is the compound of multi environment. Proper mechanism is significantly required in order to manage the complex heterogeneous data replication. This paper presents a new algorithm namely the Persistence Layer Synchronous Replication (PLSR) in order to manage the agent handling the replication. The main objective of this algorithm is to develop an adaptive persistence layer which consisted of reliable and smooth replication. It achieves faster time execution and cost minimization than that other replication processes. This algorithm also introduces a multi thread based persistence layer, which supports early binding and parallel connection to the servers. All the replication servers establish its connection through interfaces, which is furthermore, similar with the SOA (Service Oriented Architecture) and the structure is flexible enough to modify i.e.; adding and removing replication server. The performance has been compared with SQL Server in terms of transactional inserts and synchronization time. The result shows that PLSR performs outstandingly up to 83.2 % and 2.49% than that SQL server for transactional insert and time synchronization, respectively.